Analisa Pasir Pantai Bawasalo Sebagai Material Pengganti Pada Kuat Tekan Dan Kuat Tarik Belah Beton - Rusvita Rusvita; Adnan Adnan; Hamsyah Hamsyah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Bawasalo beach sand shows the potential of abundant material resources, but local people still face several considerations in the use of this material. The purpose of this research is to determine the characteristics and effect of the addition of bawa salo sand on compressive strength and split tensile strength. This research uses an experimental method carried out at the Structure and Materials Laboratory of Muhamadiyah University of Parepare using a sample of 27 cylinders with the compressive strength of the plan used is 25 Mpa. Based on the test results, the characteristics of Bawasalo beach sand have met the specifications to be used as fine aggregate for concrete mixtures. The results of normal concrete testing aged 7 days with an average of 17.41Mpa, at 28 days testing with an average of 27.77MPa, 50% variation aged 7 days with an average of 16.84MPa and 100% variation aged 7 days with an average of 13.16MPa and at 28 days testing with an average of 21.80MPa. Normal concrete testing aged 28 days 10.444 MPa, 50% variation with an average of 5.556 MPa and as for the 100% variation with an average of 3.889 MPa. Based on the results of research data analysis, compressive strength and split tensile strength decreased as the percentage of Bawasalo beach sand use increased.